ESTIMATION AND SELECTION OF CRITERIA FOR OPTIMUM CUTTING SYSTEM ACCORDING TO ENERGY-CONSUMING INDICES OF TECHNOLOGICAL EQUIPMENT - J. A. Mrochek; D. V. Adamenko; V. M. Adamenko (Наука и техника)
The paper proposes a method for calculation of optimum cutting speed with due account of energy-consuming indices of the technological equipment that makes it possible to ensure better efficiency of the technological cutting system usage from energy engineering criteria.